Creative Teaching in the Context of Educational Reform: Insights from the Perspective of In-service Teachers - Wei, Ju-Hui; Chuang, Hsueh-Hua (Journal of Education Culture and Society, 2024)
Aim. This study aims to elucidate the multifaceted nature of creative teaching within the specific context of educational reform by exploring the nuanced perspectives of in-service teachers through their real-life teaching experiences.Methods. A qualitative approach was adopted, with semi-structured, vignette-based interviews with 19 teachers from elementary, junior high, and senior high schools in Taiwan. Data analysis followed reflexive thematic analysis methods.Results. The findings underscore that in-service teachers perceive creative teaching not as the creation of entirely new educational paradigms but rather as the adoption of unconventional methods. This entails the adaptive and strategic utilisation of diverse teaching methods, the integration of multidisciplinary content, and an enduring commitment to continuous improvement. It is an incremental process involving the continuous absorption of new concepts, the adaptation of new methods, and making progressive adjustments. Conclusion. Enhancing teachers’ creative teaching requires a context-specific understanding of its essence, facilitating targeted promotion and teacher education. This study addresses the research gap by qualitatively investigating teachers’ perspectives on creative teaching and its implementation. The insights gained in this study are crucial in guiding the effective integration of creativity into pedagogical practice within teacher education and professional development endeavours.Cognitive value. This study challenges the conventional notion that creative teaching involves the invention of entirely new methods, arguing instead that creative teaching is primarily concerned with the ways in which teachers implement unconventional approaches, rather than the novelty of those approaches. These findings offer a novel perspective on fostering creative teaching within teacher development endeavours.